PANDANGAN GURU DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN KHUSUS - Sutjipto Sutjipto (Jurnal Pendidikan dan Kebudayaan, 2018)
The purpose of this research is to comprehensively examine the views of special school teachers in the development of special educational curricula on the design and principles. The research involved fourty three teachers froms eight different special schools. Data was collected through forum group discussion dan analyzed by descriptive qualitative method. The results show, first, from the teacherâ€™s point of view, that in designing a special educational curriculum for learners with special needs it should contain practical knowledge, moral character qualities and performance, essential skills, competence, art, and literacy praxis. Secondly, flexibility, functionality, independence, literacy, and vocational are the principles of developing a special education curriculum for learners with special needs.Â